2022
DOI: 10.1007/s00253-022-11988-x
|View full text |Cite
|
Sign up to set email alerts
|

A conserved subunit vaccine designed against SARS-CoV-2 variants showed evidence in neutralizing the virus

Abstract: Novel coronavirus (SARS-CoV-2) leads to coronavirus disease 19 (COVID-19), declared as a pandemic that outbreaks within almost 225 countries worldwide. For the time being, numerous mutations have been reported that led to the generation of numerous variants spread more rapidly. This study aims to establish an efficient multi-epitope subunit vaccine that could elicit both T-cell and B-cell responses sufficient to recognize three confirmed surface proteins of the virus. The sequences of the viral surface protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…A recent immunoinformatic study predicted conserved and highly immunogenic CTL-induced epitopes on S1 VRFPNITNL (327–335 aa) and PYRVVVLSF (507–515 aa) ( Table 1 ), while the CTL-induced epitopes on S2 were identified to be VVFLHVTYV (1060–1068 aa) and GVVFLHVTY (1059–1067 aa) ( Table 2 ) [ 117 ]. Based on the conservancy, antigenicity, allergenicity, population coverage and transmembrane location, another study chose potential conserved epitopes from the S1 (FNATRFASVYAWNRK, 342–356 aa) ( Table 1 ), S2 (FLHVTYVPAQEKNFT, 1062–1072 aa) ( Table 2 ) and the E/M protein to construct a SARS-CoV-2 vaccine and revealed that it had high immunogenicity and broad neutralizing activity against the SARS-CoV-2 RBD ( Figure 3 ) [ 118 ]. Jiang et al, with web-based analytic tools, also predicted potential T cell epitopes induced by the SARS-CoV-2 SP and narrowed them down to CD4 or CD8 T cell epitopes using ELIspot and a cytolytic assay [ 119 ].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%
“…A recent immunoinformatic study predicted conserved and highly immunogenic CTL-induced epitopes on S1 VRFPNITNL (327–335 aa) and PYRVVVLSF (507–515 aa) ( Table 1 ), while the CTL-induced epitopes on S2 were identified to be VVFLHVTYV (1060–1068 aa) and GVVFLHVTY (1059–1067 aa) ( Table 2 ) [ 117 ]. Based on the conservancy, antigenicity, allergenicity, population coverage and transmembrane location, another study chose potential conserved epitopes from the S1 (FNATRFASVYAWNRK, 342–356 aa) ( Table 1 ), S2 (FLHVTYVPAQEKNFT, 1062–1072 aa) ( Table 2 ) and the E/M protein to construct a SARS-CoV-2 vaccine and revealed that it had high immunogenicity and broad neutralizing activity against the SARS-CoV-2 RBD ( Figure 3 ) [ 118 ]. Jiang et al, with web-based analytic tools, also predicted potential T cell epitopes induced by the SARS-CoV-2 SP and narrowed them down to CD4 or CD8 T cell epitopes using ELIspot and a cytolytic assay [ 119 ].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%
“…The FepA protein (outer membrane protein) in Shigella is highly immunogenic [41] , [43] , with some modification and incomplete/complete adjuvant FepA hapten as a vaccine candidate tested on mice model to determine its immune responses against S. flexneri . Our previous study on multi-epitope-based synthetic vaccines also showed to produce neutralizing antibodies on Vero-2 cell culture against SARS-CoV-2 [42] .…”
Section: Discussionmentioning
confidence: 89%
“…3 e). Parker's hydrophobicity was used to identify hydrophobicity [ 49 ] the values which are −7.629 (minimum) and 7.743 (maximum). The average value was 1.34 ( Fig.…”
Section: Resultsmentioning
confidence: 99%